Importancia de los àcidos hùmicos en el cultivo de tomate ( Solanum Iycopersicum L. - Santos Franco, Edinson Dario (2019)
SUMMARY Some authors associate the positive effects of humic acids on the development of the aerial part of the plant, with the capacity of these to control the vegetal assimilation of different nutrients, or to provide a potentially assimilatible fraction of these Nutrientdeficient conditions. Pizzeghello et. Al., and Mackowiak, Grossl, & Bugbee, consider that an indirect effect of SH on plant growth constitutes the acomplejamiento of a nutrient cation by said humic acid in the growth medium, resulting in the penetration of that nutrient in the plant. According To Garcia, the basic physical and chemical properties of humic acid determine the strength of their effect on nutrient intake by the plant. Muscolo and Nardi have demonstrated the ability of humic fractions of low molar mass to accumulate in the apoplasto and enrich, at least in part, the plasma membrane. Other possibilities would be derived from an enzymatic action at the membrane level, which would generate some kind of internal messenger or active fragment, responsible for the different responses observed on different biochemical systems and metabolic processes. Intracellular. Similarities have been found between the action of acid humic and the different growth regulators such as Gibberellins, cytokinins and in particular auxins. Recently, it has been detected by mass spectrometry and immunoassay the presence of structures equivalent to indole ácetico acid in the different fractions of acid humic. This same pattern was observed for the activity H +-Atpase of the plasma membrane, allowing the authors to suppose a possible role of the humic substances extracted with water, in the modulation of the absorption of nitrate through an interaction with this enzyme. Guridi in 2000, found that humic acids extracted from a vermicompost stimulated the growth of the root system of coffee plants and increased the hydrolytic activity of ATP in vesicles of membranes obtained from these roots. However, there are works that have found a positive effect of the acid humic purified or not and applied via foliar in field conditions. Some authors have observed that the foliar application of acid humic also produces a significant increase in the development of the root and the aerial part.